2014
DOI: 10.1038/cddis.2014.174
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin deficiency aggravates hepatic injury induced by ischemia–reperfusion in mice

Abstract: Osteopontin (OPN) is a multifunctional protein involved in hepatic steatosis, inflammation, fibrosis and cancer progression. However, its role in hepatic injury induced by ischemia–reperfusion (I–R) has not yet been investigated. We show here that hepatic warm ischemia for 45 min followed by reperfusion for 4 h induced the upregulation of the hepatic and systemic level of OPN in mice. Plasma aspartate aminotransferase and alanine aminotransferase levels were strongly increased in Opn−/− mice compared with wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Pharmacological blockade of iNOS attenuates microglia activation and the expression of TNF and IL-1 in the thalamus of OPN-deficient mice (Schroeter, Zickler, 2006). In a macrophage cell line, downregulation of OPN enhances iNOS expression and leads to an upregulation of iNOS, TNF-α and IL-6 in response to lipopolysaccharides (Patouraux et al , 2014). In porcine microglia, OPN inhibits superoxide production induced by stimulation with phorbol-myristate-acetate (Tambuyzer, Casteleyn, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Pharmacological blockade of iNOS attenuates microglia activation and the expression of TNF and IL-1 in the thalamus of OPN-deficient mice (Schroeter, Zickler, 2006). In a macrophage cell line, downregulation of OPN enhances iNOS expression and leads to an upregulation of iNOS, TNF-α and IL-6 in response to lipopolysaccharides (Patouraux et al , 2014). In porcine microglia, OPN inhibits superoxide production induced by stimulation with phorbol-myristate-acetate (Tambuyzer, Casteleyn, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…In support of this notion, Zhang et al have revealed that OPN expression was increased in renal tubular epithelial cells after renal I/R in mice, which resulted in exaggerated initial inflammatory responses as mediated by the NK cell activation (31). In contrast to renal ischemia model, recent study has also demonstrated an upregulation of OPN expression in the liver tissues and plasma after hepatic I/R which were shown to play protective functions in hepatic injury and inflammation by its ability to partially prevent death of hepatocytes and to limit the production of toxic inducible nitric oxide synthase (iNOS)-derived nitric oxide (NO) by macrophages (32). Thus, the data from the above studies may suggest that OPN might play dual roles depending on ischemia and reperfusion models adopted in various organs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that OPN may serve as a biomarker of severe fibrosis and portal hypertension during Schistosomiasis mansoni (8) and chronic viral hepatitis (9,10). Nevertheless, in mice models of liver injury induced by diethylnitrosamine or ischemia/reperfusion, OPN exerted a protective effect by ameliorating the production of IL-6 and TNF-α in macrophages and inhibiting inflammation (11,12). Furthermore, OPN may serve a key role in the expansion of hepatic progenitor cells (HPC) and in promoting liver regeneration during liver cancer (13,14) and acute liver failure (15,16).…”
Section: Introductionmentioning
confidence: 99%